Analysis of Cognitive Development Theory by Jean Piaget on Color Games on Early Childhood Development - Indriyani, Ratih; Taswadi; Sobandi, Bandi (EduLine: Journal of Education and Learning Innovation, 2024)
This study analyzes the application of Jean Piaget's cognitive development theory through color play in early childhood development. This study uses a systematic literature review approach with secondary data obtained from journals searched through Google Scholar, Scopus, and PubMed. A total of 10 journals met the inclusion criteria after going through the selection, coding, and quality assessment processes. The results of the analysis show that color play functions as a visual stimulus that stimulates cognitive development, including logical thinking skills, classification, and problem solving in early childhood. The main findings of this study reveal that the application of Jean Piaget's theory through color play has a significant effect on children's cognitive and fine motor development. This study emphasizes the importance of learning media that are adjusted to the child's developmental stage to increase the effectiveness of learning.